Ngemong: Dimensi Keluarga Pasien Psikotik di Jawa - M A Subandi (Faculty of Psychology, Universitas Gadjah Mada, 2008)
The purpose of this paper was to explore family burden, coping, and support for psychotic patients in a Javanese setting. A combination of ethnographic and clinical methodology was employed. During my fieldwork in Yogyakarta, Indonesia, I followed 9 participants diagnosed as having first episode psychosis. Three of them met the ICD-10 criteria for Schizophrenia, five for Acute and Transient Psychotic Disorder (ATPD), and one for Schizoaffective Disor¬der. I carried out ethnographic fieldwork among nine participants and their families in their natural home setting, as well as conducting in-depth interviews. In addition, I administered the Family Crisis Oriented Personal Evaluation Scale (F-COPES) for family members and Sentence Completion Test (SCT). The result indicated that despite experiencing psychological and economic burden, families provided a high level of support for their mentally ill members which are reflected in the application of Javanese principle of ngemong. Three aspects the practice of ngemong is discussed. Keywords: family, psychotic illness, bur¬den, coping, support, Javanese culture